Instabilidade difusiva em um modelo presa-predador generalista - Rodrigues, Vagner Weide (2017)
In this work, we investigate the pattern formation of a reaction-diffusion generalist predator-prey system with constant alternative food source and a Holling type III functional response. The local model can exhibit up to six equilibria, bistability, limit cyles and several bifurcations. We analyse diffusive instability conditions and verify the spatial distribution of preys and predators in a two-dimensional habitat with reflective zero-flux boundary conditions. We investigate the spatial behavior for three parameters combinations: Case 1: single coexistence equilibrium; Case 2: bistability; and Case 3: bistability and limit cycle. This work is divided as follows: nn Chapter 1, we present the stability analysis of the local model; in Chapter 2, we consider the movement by diffusion and find diffusive instability conditions; lastly, in Chapter 3 we perform extensive numerical simulations in order to investigate the spatial distribution of preys and predators.